Ð‘Ð¸Ð¾Ñ„Ð¸Ð·Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ Ñ…Ð°Ñ€Ð°ÐºÑ‚ÐµÑ€Ð¸ÑÑ‚Ð¸ÐºÐ¸ Ñ„Ð¾Ð»Ð»Ð¸ÐºÑƒÐ»ÑÑ€Ð½Ð¾Ð¹ Ð¶Ð¸Ð´ÐºÐ¾ÑÑ‚Ð¸ ÑÐ¸Ñ‡Ð½Ð¸ÐºÐ° Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð´Ð¾ Ð¸ Ð¿Ð¾ÑÐ»Ðµ Ð½Ð¸Ð·ÐºÐ¾Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð½Ð¾Ð³Ð¾ ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ - Todrin, A. F.; Chub, N. N.; Lipina, O. V.; Chekanova, V. V.; Nipot, E. E.; Pinyaev, V. I.; Todorov, P.; Gorobchenko, O. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
In the work the basic biophysical parameters of human follicular fluid prior to and after cryopreservation have been investigated. It has been shown an insignificant effect of cryopreservation on osmotic pressure, pH and density of follicular fluid, and a dynamic viscosity of cryopreserved follicular fluid increases approximately by 40%.